INFLUENCE OF NURSING CLINICAL PATHWAY IMPLEMENTATION TO LENGTH OF STAY OF NON HEMORRHAGIC STROKE PATIENTS IN BUKITTINGGI ACHMAD MOCHTAR HOSPITAL - rezkiki, fitrianola (LLDIKTI Wilayah X, 2018)
Lenght of stay is indicator of serving quality and nursing care to measure hospital efficiency level. Neurology ward is one of the wards that experience increasing of length of stay from 5,91 to 7,38. The cause of length of stay increasing is nursing care management that according to Calhoun can be formulated to nursing clinical pathway. The purpose of this study is to analyze influence of nursing clinical pathway implementation to length of stay of non hemorrhagic stroke patients in neurology ward Bukitttinggi Achmad Mochtar Hospital. The designs of this study used non-equivalent post test only control group design approach. Sample of this study were taken by purposive sampling with total of 32 samples consist of 16 sample as intervention group and another 16 samples as control group. Data analyzing used t-test independent. The result shows that there is significant influence for average length of stay of stroke non hemorrhagic patients that were given nursing clinical pathway compared to the group that is not given nursing clinical pathway with p value 0,001 (p value ≤ 0,05. According to this study, hospital should implement nursing clinical pathway when doing nursing care to patients in ward and also hospital should make policy related to nursing clinical payhway implementation..